Fotosistema II y fotosíntesis artificial: buscando una nueva alternativa energética - Arismendi Romero, Graciela (2011)
With the elucidation of the crystal structure of photosystemII (PSII), an important step in the search for new environmentally friendly energy alternatives has been taken. The attempt to imitate the characteristic reaction of photosynthesis (in order to manufacture ecologically friendly fuels) could represent a new opportunity to reduce our dependence on fossil fuels.